If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + ((8 + -13) + -1(-17 + -3)) = 0 Combine like terms: 8 + -13 = -5 -3 + ((-5) + -1(-17 + -3)) = 0 -3 + (-5 + -1(-17 + -3)) = 0 Combine like terms: -17 + -3 = -20 -3 + (-5 + -1(-20)) = 0 Multiply -1 * -20 -3 + (-5 + 20) = 0 Combine like terms: -5 + 20 = 15 -3 + (15) = 0 -3 + 15 = 0 Combine like terms: -3 + 15 = 12 12 = 0 Solving 12 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7x-2=4+5x | | (X+7)(x-7)(x+49)= | | 136-x=192 | | x^6+2x^3+1= | | X^2-45=4 | | 2*1+2(11-8)+7= | | 3v=4.8 | | x^7=81x^5 | | 3/8=y/11 | | x/2=x/3-3 | | x/2=/3-3 | | 0.1(a-0.2)=1.2+2.4a | | 3y+1.3=4 | | y^2+14=18y | | 17(3)-5-7(3)=2(3)+19 | | y=39-3z | | 0.14(x+5)-.42=0.50(x+3) | | 3y-9=12y+63 | | 5(2*1.5-1)-2(3*1.5)=1 | | (2/5)=m-(1/5) | | 7x-9=9+4x | | 9x-33=87 | | 4x^2+49=25 | | 5x+39=x+19 | | (4x+1)+95=16x | | (-3)*(-y)= | | -3f=20-f | | 6x-8x+7=x-3+10 | | (x+3)1/2=(x+5)-3/71/7 | | -11.2+8.4+4q=-.8 | | 136=4(7)(4)+2(4)(h) | | 4(x+3)+2=4x+4 |